Potensi Penambahan Kombinasi Bakteri Pelarut Fosfat dan Penambat Nitrogen terhadap Jumlah Daun dan Lebar Daun Cabai Rawit Varietas Dewata F1: Potential of Adding a Combination of Phosphate-Solubilizing and Nitrogen-Fixing Bacteria to the Number of Leaves and Leaf Width of Dewata F1 Variety of Cayenne Pepper - Ikramullah, Fiza; Rahmawati; Khotimah, Siti; Mukarlina (Life Science, 2025)
The combination of phosphate-dissolving and nitrogen-fixing bacteria can increase plant productivity and nutrient availability as an environmentally friendly biofertilizer candidate. The purpose of the study was to determine the effect of a combination of bacterial strains P1, P2, P3, N1, N2, and N3, on the growth of cayenne pepper, and to determine the best treatment of the combination of bacterial strains. The research was conducted from May to August 2023. The research was carried out by watering bacterial isolates on the cayenne pepper planting media. Observations were made for 2 months after transplanting. Data analysis used a completely randomised design with 9 treatment levels, namely, KP, KN, A (P1+P2+P3+N1); B (P1+P2+P3+N2); C (P1+P2+P3+N3); D (PI+P2+P3+N1+N2); E (P1+P2+P3+N1+N3); F (P1+P2+P3+N2+N3); G (P1+P2+P3+N1+N2+N3), with 4 replications. The results showed that the combination of phosphate-solubilising bacteria strains (P1, P2, P3) and nitrogen-fixing bacteria strains (N1, N2, N3) had a significant effect on the parameters of the number of leaves and leaf width of cayenne pepper (Capsicum frutescens L.). Treatment A (P1+P2+P3+N1) is a combination of bacterial strains that gives the best results on leaf width (5.20 cm) and number of leaves (47.75 strands). This biofertilizer enhances plant productivity and prevents environmental pollution.